The economy of the Middle East and North Africa in 1997 - El-Erian, Mohamed A. 1958- (International Monetary Fund, 1997)
The economy of the Middle East and North Africa improved considerably in 1996, and remained favorable in 1997. This paper, by Mohamed A. El-Erian and Susan Fennell, presents an assessment of the recent experience of the MENA economies and examines prospects for 1998 and beyond